Cross-country analysis of national mental health investment case studies in sub-Saharan Africa and Central, South and South-East Asia - Chisholm, Dan; Lee, Yong Yi; Baral, Phanindra Prasad; Bhagwat, Sadhana; Dombrovskiy, Vladislav; Grafton, Daniel; Kontsevaya, Anna; Huque, Rumana; Kalani Okware, Kenneth; Kulikov, Alexey; Marahatta, Kedar; Mavunganidze, Patience; et al. (Frontiers in Health Services, 2023)
Introduction Despite the increasing interest in and political commitment to mental health service development in many regions of the world, there remains a very low level of financial commitment and corresponding investment. Assessment of the projected costs and benefits of scaling up the delivery of effective mental health interventions can help to promote, inform and guide greater investment in public mental health. Methods A series of national mental health investment case studies were carried out (in Bangladesh, Kenya, Nepal, Philippines, Uganda, Uzbekistan and Zimbabwe), using standardized guidance developed by WHO and UNDP and implemented by a multi-disciplinary team. Intervention costs and the monetized value of improved health and production were computed in national currency units and, for comparison, US dollars. Benefit-cost ratios were derived. Findings Across seven countries, the economic burden of mental health conditions was estimated at between 0.5%–1.0% of Gross Domestic Product. Delivery of an evidence-based package of mental health interventions was estimated to cost US 0.40–2.40 per capita per year, depending on the country and its scale-up period. For most conditions and country contexts there was a return of >1 for each dollar or unit of local currency invested (range: 0.0–10.6 to 1) when productivity gains alone are included, and >2 (range: 0.4–30.3 to 1) when the intrinsic economic value of health is also considered. There was considerable variation in benefit-cost ratios between intervention areas, with population-based preventive measures and treatment of common mental, neurological and conditions showing the most attractive returns when all assessed benefits are taken into account. Discussion and Conclusion Performing a mental health investment case can provide national-level decision makers with new and contextualized information on the outlays and returns that can be expected from renewed local efforts to enhance access to quality mental health services. Economic evidence from seven low- and middle-income countries indicates that the economic burden of mental health conditions is high, the investment costs are low and the potential returns are substantial.